The Criminal Proof Mechanism for Gorilla Tobacco-Type Drug Crimes Under Guideline Number 11 of 2021 in Indonesia - Sianturi, David; Hikmah, Faidatul (Jurnal Ius Constituendum, 2024)
This study explores the legal intricacies of drug crimes involving substances like Gorilla Tobacco under Indonesia's Narcotics Law, aiming to address disparities in penalty severity. Employing legal normative methods, conceptual approaches, and statutory analysis, it examines key provisions of the law, particularly the proving mechanism for Gorilla Tobacco offenses and the significance of Guideline No. 11 of 2021. Emphasizing the need to standardize evidence calculation and suspect qualifications for a fair legal foundation, the research highlights the complexities in investigating and prosecuting Gorilla Tobacco-related crimes. It underscores the importance of international collaboration and community involvement in addressing these challenges. Through structured analysis, this study provides valuable insights into the evolving mechanism of criminal proof for Gorilla Tobacco offenses, advocating for fairness and effectiveness within the criminal justice system. The incorporation of Guideline No. 11 proves pivotal in this pursuit, offering a balanced response to the dynamic nature of drug-related crimes and the evolving legal landscape in Indonesia.